Effect of Dual Release Antifungal Pad on Postharvest Quality and Shelf Life of Acid Lime under Ambient Storage Conditions - Kandel, Khumananda; Timilsina, Ram Hari; Risal, Chandra; Poudel, Bishal; Khadka, Gaurav; Kadel, Sailendra (Journal of Agriculture and Forestry University, 2026)
Acid lime (Citrus aurantifolia Christm.) is an important commercial citrus fruit crop in Nepal next to mandarin. It is a non-climacteric and perishable type, having a short shelf life, and quality deteriorates rapidly after harvest. This study was conducted to evaluate the effect of sulfur dioxide (SO2) generating antifungal pads containing different concentrations of sodium metabisulfite on the postharvest quality and storage life of acid lime, and to identify the most suitable antifungal pad dose for storage. Altogether, nine treatments of SO2 pads (0.00, 1.25, 2.50, 3.75, 5.00, 6.25, 7.50, 8.75, and 10.00 g) were evaluated in a completely randomized design (CRD) with three replications. Fruits of uniform size (30-40 g) were packaged at modified atmospheric condition and stored at 32±2oC with 75±5% relative humidity. Physicochemical parameters were assessed at 1, 8, 15, 22, and 29 days after storage (DAS). Titratable acidity (TA) and total soluble solids (TSS) declined at higher doses (above 7.50 g). Results revealed that SO2 pad doses ranging from 2.5 g to 3.75 g were the most effective to reduce physiological weight loss (6.21% and 6.97%, respectively). Juice recovery percentage was highest at 3.75 g (24.70%) and 2.50 g (24.4%), while the lowest was observed at 10.00 g SO2. The highest freshness (4.65 score), and longest shelf life (33.80 days) of the acid lime fruits were observed at 2.50 g SO2 dose. Overall, lower SO2 doses (2.5-3.75 g) maintained postharvest quality and extended the shelf life of acid lime approximately by 14 days under ambient storage conditions.